THE INFLUENCE OF MAQASID SHARIAH PRACTICES ON SATISFACTION OF SHARIAH COOPERATIVE MEMBERS - Sinta Nopitasari; Risa Bhinekawati; Muhammad Najib (Al-Mubin, 2023)
This study aims at investigating the influence of five variables of Maqashid al Shariah on satisfaction of syariah cooperative members.  The study gathered 200 respondents from nine sharia cooperatives in six provinces of Indonesia.  Using multiple regression models, the collected data was tested and further analyzed using SPSS 24.0 Software.  This research found that maintaining religion, human life, lineage, and wealth have positive and significant influence the satisfaction of shariah cooperative members, with level of confidence 95%. Meanwhile, maintaining intellect has no influence on the satisfaction of shariah cooperative members with level of confidence 95%.  However, simultaneously, the five components of Maqashid al Shariah positively and significantly influence the satisfaction of shariah cooperative members with level of confidence 95%. This study contributes to the theory by giving empirical evidence that the concept of Maqashid al Shariah can be operationalized to measure satisfaction of shariah cooperative members, which has not been studied before.  In practice, the management of shariah cooperatives can adopt the model developed by this study to improve the performance of their cooperatives